Findings in Tooth Roots and Jaw Bones May Cause Cancer - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2024)
According to all the latest findings, the incidence of cancer is rising in most countries. This applies, for example, to countries with a high rate of vaccination with mRNA vaccines. These are also the countries with a high standard of conservative dentistry. This dentistry does not remove dead tissue, root foci, potentially toxic metals or foci in the jawbone, but aims to achieve a surface that is as esthetic as possible and well suitable for chewing. There is evidence in the literature that non-infectious chronic cases of osteomyelitis of the jaw (NICO, FDOK) in particular pose a risk of serious diseases, including cancer. The author had to experience this several times, one case is described. The corresponding laboratory value "Rantes" should be included in cancer prophylaxis.